Self-medication and medication storage practices among Lira University students in Lira city, Northern Uganda - Ikwara, Asher Emmanuel; Atwijukiire, Humphrey (Frontiers in Public Health, 2023)
Background: Self-medication is a global public health concern, particularly prevalent in developing nations. It involves the consumption of drugs without professional guidance, encompassing both over-the-counter and prescription medicines. Responsible self-medication can alleviate healthcare burdens, reduce costs, and empower individuals to manage minor ailments independently. However, improper self-medication practices can lead to adverse effects, contribute to antimicrobial resistance, and pose various health risks. This study aimed to evaluate the prevalence of selfmedication (SM) and related practices of storing medications among students at Lira University, located in Lira City West Division, Northern Uganda.This study adopted a quantitative cross-sectional design, focusing on students from various faculties. The sample size comprised 422 students, determined using the Kish Leslie formula. Data collection involved the administration of self-administered questionnaires, and subsequent data analysis was performed using SPSS version 25.The study involved participants from Lira University, primarily females (51.2%) with an average age of 23.82. A majority were Christians (59.7%) and single (87.9%). Most were from the Faculty of Health Sciences (63.7%), with thirdyear students being the largest group (48.3%). Regarding self-medication (SM), 74.2% practiced SM, with antibiotics (69.2%) and tablets (69.2%) being commonly self-administered. In terms of medication storage, 93.4% kept medicines at home, mostly in cupboards (76.5%), but many were unsure about proper storage practices. Participants exhibited good knowledge of SM's risks and measures to reduce it. There was a significant association between the faculty of study and SM practices (p=0.015), while other demographic factors showed no significant associations.This study sheds light on the prevalent self-medication practices among students at Lira University in Northern Uganda. Notably, antibiotics were frequently self-medicated, raising concerns about antibiotic resistance.Additionally, medication storage practices emphasize the need for proper education on storage guidelines. However, the participants exhibited good knowledge of the risks associated with self-medication, suggesting the potential for effective awareness campaigns. The study recommends targeted health education programs, stricter regulations on medication sales, improved healthcare access, proper medication disposal, further research on the factors driving self-medication, collaborative efforts, and monitoring of antibiotic use to address this public health issue effectively.